Item Nonresponse in Wages: Testing for Biased Estimates in Wage Equations - Michael Fertig; Katja Görlitz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper investigates how to test and correct for nonresponse selection bias induced by missing income information when estimating wage functions. The novelty is to use the variation in interviewer-specific response rates as exclusion restriction within the framework of a sample selection model. – – Dieses Papier untersucht, wie für Selektionsverzerrungen in Lohnfunktionen getestet werden kann, die durch fehlende Einkommensinformationen entstehen können. Das Novum dieses Papiers ist die Verwendung der interviewer-spezifischen Antwortrate als Ausschlussrestriktion bei der Schätzung eines Heckman-Selektionsmodells.
Keywords: J30; 330; Item nonresponse; wages